Cardiac Autonomic Dysfunction Is Associated With Risk of Diabetic Kidney Disease Progression in Type 2 Diabetes Mellitus - Zeng, Haixia; Liu, Jianmo; Chen, Zheng; Yu, Peng; Liu, Jianping (Frontiers in Endocrinology, 2022)
Background: Evidence on the relationship between heart rate variability (HRV) and albumin-to-creatinine ratio (ACR) combined with estimated glomerular filtration rate (eGFR) in patients with type 2 diabetes mellitus (T2DM) is rare. Thus, this study aimed to investigate the relationship between HRV and the risk of diabetic kidney disease (DKD) progression. Method: Overall, 747 T2DM patients were underwent 24-hour dynamic electrocardiograms for HRV analysis. Time-domain HRV measures included mean heart rate, standard deviation of the R-R interval (SDNN), SDNN index, root mean squared difference of successive RR intervals (RMSSD), and percent of adjacent RR intervals with a difference greater than 50 ms (PNN50). Frequency-domain measures included low frequency (LF), very low frequency (VLF), high frequency (HF) and LF-to-HF ratio. The risk of DKD progression was determined by combining ACR and eGFR and stratified as low risk (Group A), moderately increased risk (Group B), high risk (Group C), and very high risk (Group D) based on the Kidney Disease: Improving Global Outcomes guidelines. Result: There were significant differences in HRV parameters among the four risk groups (SDNN: 113 ms vs 109 ms vs 101 ms vs 81 ms, P<0.01; LF: 240.2 ms2 vs 241.1 ms2 vs 155.2 ms2 vs 141.9 ms2, P<0.01; LF-to-HF ratio: 1.70 vs 1.24 vs 1.12 vs 0.93, P<0.01; VLF: 723.7 ms2 vs 601.1 ms2 vs 446.4 ms2 vs 356.3 ms2, P<0.01). A very high risk of DKD progression was significantly associated with a lower SDNN (β=-19.5, 95% CI: -30.0 to -10.0, P<0.01), and moderately increased, high, and very high risks were associated with lower LF-to-HF ratio and VLF (P<0.05). Logistic regression analysis showed that group D had a higher risk of reduced SDNN, LF-to-HF ratio, and VLF compared with group A after adjusting for systolic blood pressure, glycated haemoglobin, haemoglobin, high-density lipoprotein cholesterol, and age (odds ratio (95% CI): 0.989 (0. 983–0.996), 0.674 (0.498–0.913), and 0.999 (0.999–1.000), respectively). Conclusion: Cardiac autonomic dysfunction is associated with a risk of DKD progression in adults with T2DM, and reduced heart rate variability increased such risk. Thus, HRV screening may be necessary in patients with T2DM, especially those with high proteinuria.